Pirstoutuvatko työurat? Teollisuusalat talouden ja teknologian murroksissa - Ojala, Satu; Pyöriä, Pasi (Tampere University Press, 2020)
"The stability and quality of work careers are major social and economic issues, as the funding of the Nordic welfare state is based on the employment of working-age people and the tax revenue collected from work, production and consumption. This edited volume examines how work careers have developed in specific industrial sectors and at different levels of education in recent decades. The research results are based on the linked employer-employee data of Statistics Finland, company statistics and interviews with industry experts. Careers are examined from several different perspectives, including career stability, employment status, income development, mobility between industries and places of work, and on-the-job training. Based on the results, careers have not weakened between cohorts on average in Finland. Instead of the often-expressed perception of greater job instability, there is high stability of employment combined with high mobility within the careers, owing to the high frequency of changing industries and jobs. However, the career development of women and the low-skilled lags behind that of men and the more highly educated, meaning that equality in earnings has not progressed. Other key findings of the study suggest that adult education differs according to the level of education, and that companies' investments in intangible capital anticipate positive career outcomes for employees."